The Grammar of Catholic Schooling and Radically “Catholic” Schools - Scanlan, Martin (Catholic Education: A Journal of Inquiry and Practice, 2008)
A “grammar of Catholic schooling” inhibits many elementary and secondary Catholic schools from reflecting on how they practice Catholic Social Teaching (CST). The values of human dignity, the common good and a preferential option for the marginalized are central to CST. Schools can live these values by serving children who live in poverty, are racial, ethnic, and linguistic minorities, or have disabilities. This article demonstrates how a grammar of Catholic schooling has allowed Catholic schools to fall into recruitment and retention patterns antithetical to CST. Drawing upon a multicase, qualitative study of three urban Catholic elementary schools serving marginalized students, the article illustrates how select Catholic schools are breaking the grammar of Catholic schooling by practicing CST. Implications for research and practice are discussed.